An integrated marketing communication campaign for Uptown Mall Bonifacio - Tenorio, Alice Katherine (Animo Repository, 2016)
With significant endeavor to assess the business and marketing strategy in gauging the consumer behavior in positioning the newly opened Uptown Mall, it evaluates the omni-channel model, which allows the mall-goers to switch seamlessly between retail brands in a number of different ways. (Euromonitor International, 201) With the business objectives of sustaining and retaining the current tenant mix and acquisition of more tenants to have 100% mall occupancy, the marketing mix will be directed to the target market, which are the existing tenants. Target market and target audience were differentiated and explained. Target audience being the consumers, aged 25-34, one of the highest income distributors in the country, are the ones that impact the tenants, which will help the mall reach its target revenue. By understanding and assessing the target audience, who are the growing privileged older millennials in the country. It will solidify the mall concept aligning it to the target market, which is the existing tenant mix and cogitating the recommended list of personal services, mall activities and brand experiential campaign to propose to the target retail partners or tenants. The recommended 6-month integrated marketing campaign focuses on the online behavior of the target audience to align with the target market, which are the mall tenants. A consumer insights survey and storeowners survey were done to combine the insights of the two and align with its business and creative objectives.